A King, Poet and Scientist Who Won the Love of Generations - Dilrabakhon Ergasheva (Zien Journals, 2022)
Every nation has great kings, great scientists, great writers and poets who clearly define its historical, cultural and national image. Zahiruddin Muhammad Babur also has his place among such great children of humanity who belong to eternity. In the history of humanity, there are very few people with exceptional personal capabilities, talents and qualities like Baburcha. Babur was a great king, a classic poet, theoretician, literary critic, jurist, linguist, art critic, ethnographer, and animal and plant scientist, and he had multifaceted activities and creativity. "Boburnoma" alone is a clear example of his interest in more than twenty fields.
Keywords: Boburnoma; Zahiriddin Muhammad Babur; the great king; linguist